Surgical Treatment of Rhegmatogenous Retinal Detachment Based on Simultaneous Vitrectomy and Cataract Phacoemulsification - A. V. Malyshev; S. A. Sai; A. S. Golovin (Oftalʹmologiâ)
Purpose: To develop a method for simultaneous vitrectomy (VE) and cataract phacoemulsification (PEC) in surgical treatment of rhegmatogenous retinal detachment (RRD) complicated by proliferative vitreoretinopathy (PVR).Materials and methods. We observed 113 patients (113 eyes) aged 34 to 77 years (mean age 56.4 ± 1.9 years). Inclusion criteria for the study: total RRD complicated by stage B-C PVR, presence of a native lens, no history of previous surgical interventions for RRD. Surgical intervention was performed using the Alcon Constellation Vision System ophthalmologic surgical system, USA, and the Leica Proveo 8 microscope, Switzerland. The ophthalmologic status was assessed using standard methods based on ultrasound (Quantel medical compact touch, France), photo registration of the fundus condition and OCT of the macular area (on the Topcon 3D OCT-1 Maestro tomograph, Japan). A phacovitrectomy (PVE) technique was developed, illustrated by the techniques of the main stages of the operation.Results and discussion. The obtained results of examining patients during the observation period of up to 6 months from the moment of silicone oil removal indicate that the use of the developed technique ensures complete anatomical attachment of the retina in 92 % of cases (104 patients). The main advantages of the developed technique are explained by the fact that removal of the lens before performing PVE improves visualization of the posterior pole, as well as the peripheral part of the retina, providing good access to the base of the vitreous body. Intraoperative cataract complications, such as rupture of the posterior capsule, do not cause concern, since the vitreoretinal surgeon has the ability to immediately solve such problems. When VE and cataract surgery are performed separately, the patient is sedated or anesthetized at least twice, and possibly three times if silicone oil removal is performed separately, which generally increases the anesthesia-related risks and overall treatment costs (hospitalization, visits, medications).Conclusion. To date, there is no clear indication in the literature whether VE should be performed primarily without lens surgery or whether combined FVE may be a better strategy. The authors of this paper believe (based on the proposed surgical technique) that FVE is appropriate for RRD complicated by PVR.